JURISDICTION OVERVIEW OF VILLAGE FUND MANAGEMENT IN TRIHARJO VILLAGE SLEMAN DISTRICT, SLEMAN REGENCY - Chandra Kusuma Prabawa (Fox Justi : Jurnal Ilmu Hukum, 2020)
This study aims to find out how the management of Village Funds in Triharjo Village, Sleman District, Sleman Regency based on Government Regulation Number 60 of 2014 in conjunction with Government Regulation Number 22 of 2015 concerning Village Funds Sourced from the State Revenue and Expenditure Budget and the obstacles that arise in managing the Fund. the village. The research carried out by the author is included in the type of empirical legal research that is descriptive in nature, using a qualitative approach, namely a research method that produces analytical descriptive data, namely what is stated by the respondent in writing or orally and also real behavior, which is researched and studied as something that intact. This study uses primary data and secondary data. Data collection techniques in this study are interviews and observation. Based on the results of the research and discussion, it can be concluded that the management of Village Funds in Triharjo Village, Sleman District, Sleman Regency has been in accordance with the applicable law, but in its management it does not escape from the obstacles that occur where the hamlets receive stimulant funds disbursed by Triharjo Village in There is often a delay in submitting reports, this happens because the hamlet is not used to the existence of the Village Fund. So there is a need for socialization related to the technical implementation of Village Fund management which is carried out regularly so that its implementation is in accordance with what is stipulated in the relevant regulations. Based on the results of the research and discussion, it can be concluded that the management of Village Funds in Triharjo Village, Sleman District, Sleman Regency has been in accordance with the applicable law, but in its management it does not escape from the obstacles that occur where the hamlets receive stimulant funds disbursed by Triharjo Village in There is often a delay in submitting reports, this happens because the hamlet is not used to the existence of the Village Fund. So there is a need for socialization related to the technical implementation of Village Fund management which is carried out regularly so that its implementation is in accordance with what is stipulated in the relevant regulations. Based on the results of the research and discussion, it can be concluded that the management of Village Funds in Triharjo Village, Sleman District, Sleman Regency has been in accordance with the applicable law, but in its management it does not escape from the obstacles that occur where the hamlets receive stimulant funds disbursed by Triharjo Village in There is often a delay in submitting reports, this happens because the hamlet is not used to the existence of the Village Fund. So there is a need for socialization related to the technical implementation of Village Fund management which is carried out regularly so that its implementation is in accordance with what is stipulated in the relevant regulations. However, in its management, there are obstacles that occur where the hamlets who receive stimulant funds disbursed by the Triharjo Village in submitting their reports often occur delays, this happens because the hamlets are not familiar with the Village Fund. So there is a need for socialization related to the technical implementation of Village Fund management which is carried out regularly so that its implementation is in accordance with what is stipulated in the relevant regulations. However, in its management, there are obstacles that occur where the hamlets who receive stimulant funds disbursed by the Triharjo Village in submitting their reports often occur delays, this happens because the hamlets are not familiar with the Village Fund. So there is a need for socialization related to the technical implementation of Village Fund management which is carried out regularly so that its implementation is in accordance with what is stipulated in the relevant regulations.